Evaluation of gender-specific aspects in quality-of-life in patients with larynx carcinoma. (1st December 2016) - Tan, Sarah; Duong Dinh, Thien An; Westhofen, Martin
Abstract: Conclusions: The results suggest that gender-specific differences in health-related quality-of-life (HRQoL) exist in patients with larynx carcinoma. In previous studies these differences might have been concealed by predominantly male subject groups. Future studies should consider a gender-specific analysis that suits the patient's idiosyncrasies associated with laryngeal cancer. Objectives: There is little research concerning gender differences in quality-of-life (QoL) in patients with larynx carcinoma. Since laryngeal cancer is predominantly found in males, most studies examining HRQoL are based on a mainly male subject group. HRQoL needs to be assessed to determine the impact of disease and treatment and to evaluate possible treatment regimes. This study examined gender differences concerning HRQoL in 53 patients using EORTC QLQ-C30, and QLQ-H&N35 questionnaires. Methods: Patients treated with larynx carcinoma were given two questionnaires to assess HRQoL. The questionnaires were analyzed for each sex separately, as well as for the entire population. Results: Female patients report significantly worse HRQoL than males. Age could not be identified as a significant predictor for HRQoL when males and females were analyzed together, and does not significantly predict HRQoL in men. However, age was found to be a significant predictor for HRQoL when only females were analyzed.